THE NOTION OF GRIEVANCE AS A LIMITING CRITERIA IN THE PROCESSING OF APPEALS AND CASSATION - Rodríguez Campos, Alex (2025)
This article critiques how grievance (the harm justifying an appeal) works in Costa Rican criminal procedure. Currently, courts -especially the Cassation Chamber -reject appeals because lawyers don't "sufficiently" explain how judicial errors affected them. The problem is that nobody knows what "sufficiently" means, turning this into an arbitrary barrier to justice. The author proposes that tribunals should determine whether errors are serious once appellants clearly identify them. He also suggests eliminating rejections for "poorly explained grievance" and requiring judges to decide cases on their merits.